Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10461-012-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

High Acceptability of a Vaginal Ring Intended as a Microbicide Delivery Method for HIV Prevention in African Women

Abstract: Vaginal rings (VRs) are new methods for continuous delivery of microbicides. This is the first study to quantitatively and qualitatively explore the acceptability of rings in Africa: 157 HIV-negative, sexually active women aged 18-35 used a placebo silicone elastomer ring for 12 weeks. They completed product acceptability questionnaires every 4 weeks. We conducted 6 exit focus group discussions with a subset of 48 women and 19 in-depth interviews with male partners. Retention in the study was high (97 %). Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 24 publications
7
95
0
Order By: Relevance
“…Thus, it is reasonable to assume that it will be easier for women to adhere to long-duration IVR delivery systems compared with daily, episodic, or coitally dependent gels. This is supported by the fact that IVRs have seen excellent product demand and commercial success as a form of birth control in high-income countries and are gaining acceptance in low-income countries (7,29).…”
Section: Significancementioning
confidence: 98%
“…Thus, it is reasonable to assume that it will be easier for women to adhere to long-duration IVR delivery systems compared with daily, episodic, or coitally dependent gels. This is supported by the fact that IVRs have seen excellent product demand and commercial success as a form of birth control in high-income countries and are gaining acceptance in low-income countries (7,29).…”
Section: Significancementioning
confidence: 98%
“…Subsequent research has found that although many women appreciate a product they can use without a partner's knowledge [27], microbicide trial participants typically talked with their steady partners about the product [3, 6, 812]. Moreover, male partners’ awareness and acceptance of product use influenced trial participants’ product acceptance and self-reported adherence [7, 1316].…”
Section: Introductionmentioning
confidence: 99%
“…During pre-clinical or clinical trials, acceptability of the candidate microbicides of nonoxynol-9 [15, 16], cellulose sulfate [17], BufferGel [9, 18, 19], PRO 2000 Gel [1820], a vaginal ring microbicide delivery modality [21], and tenofovir [2224] were examined. In what follows, we briefly review acceptability data for each of the candidate microbicides.…”
Section: Introductionmentioning
confidence: 99%
“…An additional study examined the acceptability of a vaginal ring to continuously deliver microbicides via a mixed-methods design among HIV-negative, sexually active women and their male partners [21]. The majority of women (69%) reported high levels of interest in trying the vaginal ring and liked the possibility that the ring could prevent HIV and not interfere with sexual activity [21].…”
Section: Introductionmentioning
confidence: 99%